Factors influencing weight control practices amongst the adolescent girls in Vhembe District of Limpopo Province, South Africa - Rose A. Tshililo; Lizzy M. Netshikweta; Grace T. Tshitangano; Hilda L. Nemathaga (AOSIS, 2016)
Background: The incidence of overweight is increasing amongst adolescents in many countries around the world. Healthy and unhealthy weight control practices are common amongst overweight and non-overweight adolescents. Aim: The aim of this study was to explore factors influencing weight control practices amongst adolescent girls. Setting: The study was conducted at selected secondary schools of Vhembe District of Limpopo Province, South Africa. Methods: A qualitative, exploratory, descriptive and contextual design was used. Nonprobability, purposive sampling was used to select adolescents who are practicing weight control. In-depth interviews were conducted with 30 participants. Data were analysed according to Tesch's open-coding method. Results: This study revealed that adolescent girls are influenced by a variety of factors to control their weights. These included individual factors, such as body image dissatisfaction; family factors, caused by parental criticism about adolescent weight; and environmental factors, which contain peer group endorsement of dieting. Conclusion: Adolescents are exposed to many unhealthy weight control practices, as a way of controlling excess weight. So it is of importance for healthcare providers to make them aware of healthy practices.